GAYA BAHASA PERULANGAN DAN NILAI RELIGIUS PADA ANTOLOGI PUISI “SANG PENCIPTA, CINTA, DAN RENUNGAN KEHIDUPAN”KARYA Dr. ANIK PUJI RAHAYU M.Kep (KAJIAN STILISTIKA) - alfina oktavianti (sarasvati, 2024)
This research discusses the language style of repetition and religious values in the poetry anthology entitled "The Creator, Love, and Reflections on Life" by Dr. Anik Puji Rahayu M.Kep. The aims of this research are (1) to describe the types of repetitive language styles (2) to describe the religious values contained therein. It is hoped that this research will be useful for students to broaden their knowledge and insight, and also be useful for other researchers as reference or comparison material who will later research similar things. This type of research uses a qualitative approach. The data source taken by the researchers came from a poetry anthology by Anik Puji Rahayu. Data in the form of words, phrases, sentences and stanzas contained in the poetry anthology. Data collection techniques were carried out for more than 1 month, from March 14 – April 25 2024 using documentation techniques, note. Data analysis techniques by reading and recording in more depth. The results of research in the analysis of the poetry anthology show that the language styles of repetition that are most often used are the repetition language styles of epizeukis, anaphora and assonation. Likewise with the religious value contained in it, in this poetry anthology there are many stanzas that express gratitude, acknowledgment of God's goodness, and acceptance of fate.Keywords: repetitive language style, religious values, poetry anthology